PENILAIAN KEBERLANJUTAN PENGELOLAAN SISTEM PENYEDIAAN AIR MINUM BERBASIS MASYARAKAT DI KOTA BLITAR - Puji Kamulyan; I Putu Artama Wiguna; Agus Slamet (Institut Teknologi Sepuluh Nopember, 2017)
The paper disccuses an assess the sustainability level, to identify important and priority factors of Community Based Water Supply System (CBWSS) management. Public and stakeholders perception are the main data needed for the analysis, and these data are collected through observation and structured interviews. The consideration aspects to measure the sustainability level consist of technical,institutional, financial, social and environmental aspects.This study used several analysis methods, i.e. Index Formulation (measuring sustainability level), Relative Importance Index and Confidence Interval (identifying important factors) and Development Priority Index (determining priority factors).The results indicate that CBWSS management is generally quite sustainable, with the highest sustainability value on environmental aspect, while the lowest one is on social aspect. The most important factor in the CBWSS management is the existence of community retribution and the development priority factor lead to the management transparency.